ENDOVASCULAR INTERVENTIONS IN CAROTID ARTERIES IN PATIENTS WITH CORONARY ARTERY DISEASE (Global Conference on Medical and Health Sciences, 2026)
Carotid artery stenosis is a major contributor to ischemic stroke and is commonly associated with coronary artery disease (CAD), particularly in the setting of multifocal atherosclerosis [1,2]. This study aimed to assess the safety and efficacy of carotid artery stenting (CAS) in patients with symptomatic and asymptomatic carotid stenosis and concomitant CAD. A total of 55 patients treated between 2021 and 2024 were included. The mean age was 65.5 ± 4.5 years, and the degree of internal carotid artery stenosis ranged from 40% to 99%. Most patients had significant comorbidities, including arterial hypertension (76.3%), diabetes mellitus (41.8%), and a history of myocardial infarction (30.9%). All patients received dual antiplatelet therapy prior to intervention. A total of 57 CAS procedures were performed using self-expanding nitinol stents and embolic protection devices. The technical success rate was 100%, with effective restoration of vessel patency in all cases. Pre-dilatation was required in patients with critical stenosis. No major neurological complications, myocardial infarctions, or in-hospital mortality were observed. Transient neurological deficits occurred in 12.7% of patients, with complete recovery during hospitalization. Carotid artery stenting is a safe and effective minimally invasive method for stroke prevention in patients with CAD and carotid artery disease. It may serve as a viable alternative to surgical treatment, particularly in high-risk patients with multifocal atherosclerosis [3].
Keywords: carotid artery stenosis; carotid artery stenting; coronary artery disease; multifocal atherosclerosis; endovascular treatment; embolic protection devices; ischemic stroke